Aligning Partial Defences to Murder with the Offence of Coercive or Controlling Behaviour. (February 2019) - Bettinson, Vanessa
This article will reflect on the adoption of s. 76 Serious Crime Act 2015 which criminalises coercive or controlling behaviour in an intimate or family relationship and considers an argument for aligning partial defences to murder with it. It takes inspiration from the case of Sally Challen, granted leave to appeal her murder conviction at the Court of Appeal on 1st March 2018. Leave was granted after her lawyers successfully persuaded the court that the introduction of s. 76 Serious Crime Act 2015 amounted to fresh evidence in her defence that was unavailable at the time of her trial in 2011. Lady Justice Rafferty stated that, "It should be plainly understood that the application made today is but one step in what, it is hoped by counsel, those who instruct her and many others concerned in this case, will be a full detailed exploration of the position, based on scholarship, learning and clinical expertise, which should prevail now… A jury, it is argued, should, with the benefit of that learning, be enabled to reach a clear settled conclusion on the basis of an understanding which, it is said, was not available to the jury in 2011." The arguments at her appeal will seek to reduce her murder conviction to manslaughter, providing an opportunity for this article to explore the complexities of aligning the partial defences to murder with the offence of coercive or controlling behaviour.